The Imbalance of Circulating Follicular Helper T Cells and Follicular Regulatory T Cells Is Associated With Disease Activity in Patients With Ulcerative Colitis - Long, Yan; Xia, Changsheng; Xu, Lijuan; Liu, Caoyi; Fan, Chunhong; Bao, Huizhang; Zhao, Xiaotao; Liu, Chen (Frontiers in Immunology, 2020)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease affecting the colon and rectum, and the abnormality of B cells is involved in the pathogenesis and progression of UC. Follicular helper T cells (TFH) play an important role in assisting the immune function of human B cells in germinal centers, and follicular regulatory T cells (TFR) have the function of inhibiting TFH and germinal center B cell responses. The significance of circulating TFH and TFR in ulcerative colitis (UC) remains unclear. We analyzed peripheral blood of active and stable remission UC patients and found that circulating TFR was significantly decreased while TFH was increased in active UC patients. As to TFH subsets, TFH2 was elevated while TFH17 was decreased in active UC, with IL-4/IL-17 secretion enhanced. Helios+ and CD45RA-FoxP3high TFR cells were decreased while CD226+ and CD45RA+FoxP3int TFR cells were increased in active UC patients. The levels of new memory B cells, plasmablasts and serum IgG were significantly increased in active UC patients, and were positively correlated with TFH, TFH2 and negatively correlated with TFR. Serum CRP and Mayo Clinic scores were positively correlated with TFH and TFH2 but negatively correlated with TFR. Serum IL-12 and IL-21 were up-regulated while IL-10 was down-regulated in active UC. To conclude, imbalance of circulating TFH and TFR cells is associated with disease activity in UC patients. Our results suggest a new mechanism for TFH and TFR imbalance in the pathogenesis of UC, providing a new perspective for theoretical research and therapeutic strategies for UC.